Nocarimidazoles C and D, antimicrobial alkanoylimidazoles from a coral-derived actinomycete Kocuria sp.: application of 1JC,H coupling constants for the unequivocal determination of substituted imidazoles and stereochemical diversity of anteisoalkyl chains in microbial metabolites - Karim, Md. Rokon Ul; Harunari, Enjuro; Sharma, Amit Raj; Oku, Naoya; Akasaka, Kazuaki; Urabe, Daisuke; Sibero, Mada Triandala; Igarashi, Yasuhiro (Beilstein Journal of Organic Chemistry, 2020)
Chemical investigation of secondary metabolites from a marine-derived actinomycete strain of the genus Kocuria, isolated from a stony coral Mycedium sp., led to the identification of two new alkanoylimidazoles, nocarimidazoles C (1) and D (2) as well as three known congeners, nocarimidazoles A (3) and B (4) and bulbimidazole A (5). Structure analysis of 1 and 2 by NMR and MS revealed that both are 4-alkanoyl-5-aminoimidazoles with a 6-methyloctanoyl or decanoyl chain, respectively. Two possible positions of the amino group on the imidazole rings (C-2 and C-5) posed a challenge in the structure study, which was settled by the measurement of 1JC,H coupling constants for comparison with those of synthetically prepared model imidazoles. The absolute configurations of the anteisoalkanoyl group present in 1, 4, and 5 were determined by low-temperature HPLC analysis of the degradation products labeled with a chiral anthracene reagent, which revealed that 1 is a mixture of the R- and S-enantiomers with a ratio of 73:27, 4 is the pure (S)-enantiomer, and 5 is the (S)-enantiomer with 98% ee. The present study illustrates the diversity in the stereochemistry of anteiso branching in bacterial metabolites. Compounds 1−4 were moderately antimicrobial against Gram-positive bacteria and fungi, with MIC ranges of 6.25–25 μg/mL.
Keywords: 1JC,H; alkanoylimidazoles; anteiso; Kocuria; nocarimidazole